Non-Traditional Security Challenges for Nepal: A Case of Covid-19 - Pant, Sambid Bilas (Unity Journal, 2022)
The security landscape has undergone profound changes since the start of the twenty-first century. Non-Traditional Security (NTS) threats other than military, political and diplomatic conflicts have greatly impacted the lives of people. Over the years, the nature of threats and security discourses have drastically changed and countries like Nepal with low human development index have been severely affected. The coronavirus COVID-19 pandemic has brought an additional dimension to security challenges. The pandemic’s impact can be felt in all aspects of life in Nepal since it is located between two South-Asian nations: China, where the outbreak was first reported and India, the second-most affected country across the world. In Nepal, COVID-19 has had an adverse impact on health, education, economy, tourism, food security, cyber security and overall development. This paper aims at critically examining the NTS approach taken by the government of Nepal and the role played by the Nepali Army (NA) to address the pandemic to ensure fundamental human rights and development. This study also aims to shed light on lessons learned from the outbreak and the future steps needed to strengthen the Global Health Diplomacy (GHD). The study is divided into four sections namely effects of covid-19, response to covid-19, overall impact at national level, suggestions and recommendations. A descriptive-analytical review of research papers, government reports, policy statements and issues papers was conducted. The paper analyzes and interprets the pandemic preparedness and response by the government and provides recommendations for strengthening health diplomacy to combat Covid-19 pandemic in Nepal.